JENIS VEGETASI DAN PERANANNYA TERHADAP SUMBER MATA AIR DI KAWASAN HUTAN LINDUNG BIFEMNASI SONMAHOLE DESA TAEKAS - Binsasi, Yeremias; Blegur, Willem Amu (Universitas Tanjungpura, 2024)
Vegetation around springs acts as a water absorber, filter and protects water quality. The presence of vegetation helps prevent erosion, waterlogging, and maintains a balanced ecosystem. This research was conducted to analyze the type of vegetation around the spring in the Bifemnasi Sonmahole Protected Forest Area, Taekas Village. The results of the research can be concluded that the type of vegetation around the Oel Lete spring has 13 types of vegetation with a total of 90 individual types and 8 families. the type Syzygium cumini with a total of 27 individuals, while the species found the least was the type Ficus variegata with the number of individuals 1. The highest INP value was Syzygium cumini (76.04%) and the one with the lowest INP was Terminalia catappa (4.75%).Keywords: Protected Forest Area, Role of Vegetation, Water sources. AbstrakVegetasi di sekitar sumber mata air berperan sebagai penyerap air, penyaring, dan melindungi kualitas air. Kehadiran vegetasi membantu mencegah erosi, genangan air, dan menjaga ekosistem yang seimbang. Penelitian ini dilakukan menganalisis jenis vegetasi sekitar sumber mata air di Kawasan Hutan Lindung Bifemnasi Sonmahole Desa Taekas. Hasil penelitian dapat disimpulkan bahwa jenis vegetasi di sekitar sumber mata air Oel Lete memiliki 13 jenis vegetasi dengan total individu 90 jenis dan 8 famili. jenis Syzygium cumini dengan jumlah individu 27 sedangkan jenis yang paling sedikit dijumpai adalah jenis Ficus variegata dengan jumlah individu 1. Nilai INP tertinggi adalah Syzygium cumini (76,04%) dan yang memiliki INP terendah adalah Terminalia catappa (4,75%).Kata kunci: Kawasan Hutan Lindung, Peran Vegetasi, Sumber mata air.